A potential of brown rice polish as a substrate for the lactic acid and bioactive compounds production by the lactic acid bacteria newly isolated from cereal-based fermented products. (November 2018) - Jukonyte, Ruta; Zadeike, Daiva; Bartkiene, Elena; Lele, Vita; Cernauskas, Darius; Suproniene, Skaidre; Juodeikiene, Grazina
Abstract: This work aims to evaluate the fermentability of brown rice polish for the growth of eleven Lactobacillus spp. and Pediococcus spp. strains in a single step process at a solid-state fermentation (SSF) conditions. In addition, technological and functional properties of the tested lactic acid bacteria (LAB) were assessed. The brown rice polish was a suitable substrate for the cultivation of newly isolated LAB without supplements. The acidification rate, lactic acid (LA) production ability, endo-xylanase and protease activities significantly ( p  < 0.001) depended on the bacterial strain and fermentation time. Some of the tested lactobacilli were the best producers of LA (up to 116.51–160.97 g/L) with higher contents of L(+)-LA (L/D ratio 1.05–4.70). In many cases, rice polish medium as a nutrient source was comparable to MRS medium for the production of metabolite with antifungal activity against Fusarium graminearum, F. avenaceum and F. nivale. The L. brevis LUHS173, L. uvarum LUHS245 and P. pentosaceus LUHS100 strains show the potential for the technological applications due to their antifungal, xylanolytic and protein degrading capacity. Highlights: The brown rice polish is suitable substrate for the production of lactic acid. Selected bacterial strains could increase the contents of essential amino acids. Rice polish is comparable to MRS for the antifungal active metabolite production. Brown rice polish could be used for the development of new functional ingredients.